First observations of temperature tolerances of adult male snow crab (Chionoecetes opilio) from the Barents Sea population and the effects on the fisheries strategy. Issue 7 (9th August 2017) - Siikavuopio, Sten Ivar; Whitaker, Ragnhild Dragøy; Sæther, Bjørn Steinar; James, Philip; Olsen, Bjørn Ronald; Thesslund, Tina; Hustad, Annette; Mortensen, Atle
ABSTRACT: This study investigates the effects of temperature on the survival, food intake, oxygen consumption and growth during long-term live holding of captive male snow crab ( Chionoecetes opilio ) (average = 0.7 kg). The crabs were held at three different temperatures, 3, 6 and 9°C. The trials were done using groups of snow crabs held in nine land-based holding tanks (three replicates per temperature treatment). The results showed that temperature had a significant effect on survival. The survival rate at 3°C (61%) was significantly higher than at 6°C (33%) and at 9°C (28%). Specific oxygen consumption rates of unfed crab at 6°C were significantly higher than at 9°C and 3°C. In summary, the current study shows that the Barents Sea snow crab have a narrow temperature range in which they thrive compared with the Barents Sea red king crab ( Paralithodes camtschaticus ). Barents Sea snow crab has similar metabolic and physiological attributes to other major snow crab populations. In conditions when ambient temperatures are approximately 6°C, it may prove beneficial for animal welfare and also be financially advantageous to reduce ambient water temperatures in live snow crab holding facilities on boat or on land.